Immune response of heifers against a Staphylococcus aureus CP5 whole cell and lysate vaccine formulated with ISCOM Matrix adjuvant - Camussone, Cecilia; Veaute, Carolina Melania Isabel; Pujato, Nazarena; Morein, Bror; Marcipar, Iván Sergio; Calvinho, Luis Fernando (2018)
Staphylococcus aureus is the most frequently isolated pathogen from bovine intramammary infections worldwide. Commercially available vaccines for mastitis control are composed either of S. aureus lysates or whole-cells formulated with traditional adjuvants. We recently showed the ability of a S. aureus CP5 whole-cell vaccine adjuvanted with ISCOM Matrix to increase specific antibodies production in blood and milk, improving opsonic capacity, compared with the same vaccine formulated with Al(OH)3. However, there is no information about the use of ISCOM Matrix for the formulation of bacterial lysates. The aim of this study was to characterize the innate and humoral immune responses induced by a S. aureus CP5 whole-cell or lysate vaccine, formulated with ISCOM Matrix after immunization of pregnant heifers. Both immunogens stimulated strong humoral immune responses in blood and milk, raising antibodies that increased opsonic capacity. Lysate formulation generated a higher and longer lasting antibody titer and stimulated a higher expression of regulatory and pro-inflammatory cytokines compared with the whole-cell vaccine.